Performance Improvement through the Unification of Islamic Work Ethics in Intellectual Capital : Comparative Study of Malaysia and Indonesia - Arifah, Dista Amalia; Budiman, Judi (UNISSULA, 2024)
This study is to investigate the distinctions between Malaysia and Indonesia as well as the contribution of Islamic work ethics and intellectual capital to the improvement of micro, small, and medium-sized enterprises (MSMEs/MSEs/UMKM) performance in both nations. The UMKM creative industry of halal products is the research population. Purposive sampling was utilized in the sample. Multiple regression is used by the analytical tool. The research findings indicate that Organizational, Relational, and Spiritual Capital all have an impact on the success of MSMEs in Indonesia. In the meantime, relational and organizational capital have an impact on Malaysian MSMEs' performance. Overall, enhancing the performance of MSMEs in Malaysia and Indonesia through the integration of Islamic work principles in intellectual capital is similar.